Analisis Kebutuhan Perawat di Instalasi Rawat Inap dengan Pendekatan Workload Indicators of Staffing Need di Rumah Sakit Umum Aulia - Sintari, Febrina; Yoshida, Eka; Indrajaya, Titus (Jurnal sosial dan sains, 2025)
Nurses constitute the largest proportion of healthcare workers in hospitals and play a crucial role in ensuring the quality of nursing care. A high workload without proper human resource planning can lead to a decline in service quality and patient safety. This study aimed to analyze the nursing workforce requirements in the Inpatient Unit of Aulia General Hospital using the Workload Indicators of Staffing Need (WISN) approach. The research employed a mixed-methods design with a sequential explanatory approach, beginning with a quantitative descriptive analysis to calculate the ideal number of nurses based on workload, followed by qualitative analysis through structured interviews to elaborate on the quantitative findings. Qualitative research subjects included the hospital director, head of human resources and general affairs, head of the human resources department, head of nursing, ward head, registration staff, staff nurses, patients, and patients’ families. The WISN calculation indicated that the ideal number of nurses in the Inpatient Unit was 18, the workload standard was determined to be 17.92, while the allowance standard was 0.11 while only 15 were available, resulting in a shortage of 3 nurses and a WISN ratio of 0.83. The qualitative analysis identified the main causes of this gap, including high direct and indirect workloads, nurses’ involvement in non-nursing tasks, and limited facilities. This study recommends several strategies, including the implementation of a middle shift to anticipate patient surges, redistribution of workload based on the WISN method supported by internal SOPs. In addition, strengthening clinical and managerial competencies, utilizing an integrated Hospital Information System (SIMRS), conducting regular workload evaluations, implementing a performance-based reward and punishment system, and investing in nursing technology are essential steps to improve efficiency and the quality of care. With these interventions, RSU Aulia is expected to reduce nurses’ workload, enhance patient satisfaction, and achieve service standards in accordance with KRIS regulations.